2013
DOI: 10.1038/emboj.2013.8
|View full text |Cite
|
Sign up to set email alerts
|

TMEM59 defines a novel ATG16L1-binding motif that promotes local activation of LC3

Abstract: Selective autophagy underlies many of the important physiological roles that autophagy plays in multicellular organisms, but the mechanisms involved in cargo selection are poorly understood. Here we describe a molecular mechanism that can target conventional endosomes for autophagic degradation. We show that the human transmembrane protein TMEM59 contains a minimal 19-aminoacid peptide in its intracellular domain that promotes LC3 labelling and lysosomal targeting of its own endosomal compartment. Interestingl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
145
0
11

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(162 citation statements)
references
References 69 publications
6
145
0
11
Order By: Relevance
“…The ATG16L1 complex serves as an E3 ligase for MAP1LC3B-I/LC3B-I to conjugate with phosphatidylethanolamine (to generate LC3B-II). 1,2,[14][15][16] As the ATG16L1 complex specifies the membrane where LC3B-I is converted to LC3B-II to start autophagosome biogenesis, [17][18][19] studies to identify the adaptor protein that recruits the ATG16L1 complex to the autophagic membrane [20][21][22][23][24][25] and to identify the origin of the autophagic membrane using ATG16L1 as an early autophagosome biogenesis marker have been emerging. [10][11][12]26 A previous study demonstrated that correct stoichiometry of ATG16L1 complex components (ATG16L1 and ATG12-ATG5) is critical for autophagosome biogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…The ATG16L1 complex serves as an E3 ligase for MAP1LC3B-I/LC3B-I to conjugate with phosphatidylethanolamine (to generate LC3B-II). 1,2,[14][15][16] As the ATG16L1 complex specifies the membrane where LC3B-I is converted to LC3B-II to start autophagosome biogenesis, [17][18][19] studies to identify the adaptor protein that recruits the ATG16L1 complex to the autophagic membrane [20][21][22][23][24][25] and to identify the origin of the autophagic membrane using ATG16L1 as an early autophagosome biogenesis marker have been emerging. [10][11][12]26 A previous study demonstrated that correct stoichiometry of ATG16L1 complex components (ATG16L1 and ATG12-ATG5) is critical for autophagosome biogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Traf3ip3 is selectively over-expressed in memory precursor CD8 1 T cells compared with terminal effector CD8 1 T cells [5]. In a recently published paper, TRAF3IP3 was found to co-precipitate with ATG16L1, a key autophagy regulating protein [6,7], and this interaction was mediated by the WD domain of ATG16L1 [8]. However, the precise functional consequences of this binding event, as well as the potential impact of TRAF3IP3 on autophagy, remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the WD domain of ATG16L1 is necessary for interaction with TRAF3IP3 through the specific ATG16L1-binding motif [8]. In .…”
Section: Impaired Autophagy and Increased Apoptosis In Traf3ip3-deficmentioning
confidence: 99%
“…Cargo is transported into the primary cilium via the Bardet-Biedl Syndrome (BBSome) complex (which also coordinates cargo attachment to microtubule motors), IFT complex A (for dynein-2-mediated retrograde transport) and IFT complex B (for kinesin-2-mediated transport to the ciliary tip) ATG proteins required for autophagosome formation are located. One such example is ATG16L, a protein that mediates the activation of membrane-bound LC3 94 and has an essential role in autophagy through modulation of nascent autophagosomal membrane elongation. 95 Upon serum withdrawal, Shh signaling promotes ATG16L recruitment to the ciliary base via IFT20-enriched vesicles, 93 demonstrating that Shh signaling and IFT collaboratively promote autophagosome formation and provide an important point of regulation for macroautophagy.…”
Section: Primary Cilia and Autophagymentioning
confidence: 99%